2019
DOI: 10.1007/s40430-019-2014-2
|View full text |Cite
|
Sign up to set email alerts
|

Surface integrity of metal matrix nanocomposite produced by friction stir processing (FSP)

Abstract: Friction-stir processing is considered a green manufacturing process of surface composite fabrication and surface modification. Surface integrity includes different parameters such as roughness, topography, microhardness, and chemical analysis, which is one of the primary features of FSP. The goal of this research is to evaluate the surface integrity of FSP on aluminum matrix nanocomposite. The main parameter effects, including rotational speed, pass number, and the traverse speed on the surface roughness, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…This is due to the reason that the 1400 rpm sample experienced high heat which softened the surface and a smooth surface was obtained, whereas the 1000 rpm sample experienced less heat and thus more roughness was obtained in this sample. Similar results were observed by Ramezani et al [46] who studied surface integrity of AA7075/SiC surface composite produced by FSP. They observed that the surface roughness of the FSPed sample reduced with an increase in rotating speed.…”
Section: Surface Roughnesssupporting
confidence: 88%
“…This is due to the reason that the 1400 rpm sample experienced high heat which softened the surface and a smooth surface was obtained, whereas the 1000 rpm sample experienced less heat and thus more roughness was obtained in this sample. Similar results were observed by Ramezani et al [46] who studied surface integrity of AA7075/SiC surface composite produced by FSP. They observed that the surface roughness of the FSPed sample reduced with an increase in rotating speed.…”
Section: Surface Roughnesssupporting
confidence: 88%
“…The tool rotated clockwise (CW) during different FSP strategies with complete overlap. In addition, according to the literature review and experimental research, machine parameters (rotational speed of 1500 rpm and traverse speed of 40 mm/min) were constant for all experiments 6,35 . The experiments were repeated in two FSP passes to evaluate the effect of the pass number.…”
Section: Materials and Procedures Of Friction Stir Processingmentioning
confidence: 99%
“…The specimen processed at 1400 rpm experiences high heat input, resulting in a softer surface. Ramezani et al [25] suggested that an increase in TRS induces plastic deformation, resulting in decreased forces and friction, which ultimately contributes to SCs with a lower SR. The significance of other FSP parameters, including TTS and GW, on SR is also supported by the ANOVA results.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Measurement of surface roughness, a crucial technical characteristic affecting the value of industrial goods, is an integral element of assessing surface quality. Ramezani et al [25] studied the surface integrity of FSP processed aluminium matrix nanocomposites. The authors studied the effects of tool rotational speed, feed rate, and FSP pass number on topography, roughness, and microhardness.…”
Section: Introductionmentioning
confidence: 99%